Similar Effects for Resting State and Unconscious Thought: Both Solve Multi-attribute Choices Better Than Conscious Thought - Hu, Fengpei; Yu, Xiang; Chu, Huadong; Zhao, Lei; Jude, Uyi; Jiang, Tao (Frontiers in Psychology, 2018)
People have a headache trouble, then put things aside and do some other things. When they are back to the decision, it may be better than they are still in contemplating to let them satisfied. The researchers proposed a hypothesis of “Deliberation- without- attention” through experimental research to study whether it is always advantageous to engage in thorough conscious deliberation before choosing. Unconscious thinking can optimize people’ behavioral decision in a complex environment and improve people’ satisfaction after making the decision. Considering that the previous study did not use the resting pattern, and the resting state is also a kind of unconscious thinking, in this paper we further add the resting state to the unconscious thinking under the distracting tasks, unconscious and conscious joint thinking, and the conscious thinking conditions, to study the unconscious thought effect and decision-making performance of four different thinking modes. We have carried out three experiments in the choice of job, using two kinds of information presentation to check the unconscious effect, and comparing the decision-making performance of different thinking patterns. The results show that the resting state and unconscious thinking have the similar effect, and the decision-making performance of different thinking mode is different.